Identification of Phytoplankton at Ephemeral Pond with Acidic pH in Bangka Regency - Andri Kurniawan; Ardiansyah Kurniawan; Robin Robin (Al-Kauniyah: Jurnal Biologi, 2023)
AbstractEphemeral waters, the temporary aquatic environment become an interesting habitat to explore extremophile organism, include phytoplankton. Furthermore, the waters have an acidic condition or low pH that impact to metabolisms, community structure, and diversity of phytoplankton. This study was conducted on June until August 2022 in Bangka Regency, Bangka Belitung Archipelago Province, Indonesia. We analyzed the phytoplankton presence at acidic ephemeral waters to indicated their potential as primary producer in food web, bioindicator, and ecological succession agent. This study was conducted by exploration method of phytoplankton diversity. The research observed and found five class and twelve genera that consist of class Chlorophyceae (genera Enteromorpha, Ankistrodesmus, Prasiola, Pleurococcus, and Coleochaete), class Rhodophyceae (genera Lemanea), class Diatoms (genera Diatoma, Synedra, and Navicula), class Xanthophyceae (genera Ophiocytium), and class Cyanobacteria (genera Oscillatoria and Anabaena). The class Chlorophyceae, genera Enteromorpha were the highest community at the both of acidic waters and they could survive at pH 3.52 + 0.5 to 3.71 + 0.8.AbstrakPerairan ephemeral, lingkungan perairan musiman menjadi suatu habitat yang menarik untuk mengeksplorasi organisme ekstremofil, termasuk fitoplankton. Lebih jauh lagi, perairan tersebut memiliki kondisi asam atau pH rendah yang berdampak pada metabolisme, struktur komunitas, dan diversitas fitoplankton. Penelitian ini dilaksanakan pada Juni hingga Agustus 2022 di Kabupaten Bangka, Provinsi Kepulauan Bangka Belitung, Indonesia. Kami menganalisis keberadaan fitoplankton di perairan ephemeral asam untuk mengindikasikan potensi fitoplankton sebagai produsen utama, bioindikator dan agen suksesi lingkungan. Penelitian ini dilaksanakan dengan metode eksplorasi diversitas fitoplankton. Penelitian ini mengobservasi dan menemukan lima kelas dan dua belas genus yang terdiri atas kelas Chlorophyceae (genus Enteromorpha, Ankistrodesmus, Prasiola, Pleurococcus, dan Coleochaete), kelas Rhodophyceae (genus Lemanea), kelas Diatoms (genus Diatoma, Synedra, dan Navicula), kelas Xanthophyceae (genus Ophiocytium), dan kelas Cyanobacteria (genus Oscillatoria dan Anabaena). Kelas Chlorophyceae, genus Enteromorpha adalah komunitas tertinggi pada kedua perairan asam dan mampu bertahan pada pH 3.52 + 0.5 to 3.71 + 0.8.